Alternative graphemics. Aztec writing system as a case study towards an integrated, digitalised model of non-typographic graphemics - Antonio Perri; Luciano Perondi; Daniele Capo; Roberto Arista; Giampiero Dalai (Ocula)
Aztec pictographic writing conveys semantic (and linguistic) contents through conventional patterns of units. We argue that relevant visual values are ordered in subsets (topological, spatial and logical). Each unit is a "character" (in the Unicode vocabulary), either as a positive unit (a graphic sign) or as an "empty" spatial, topo-graphical relation between signs. It is sketched, then, a digital method processing sets of basic graphic features as non-linear combinations of variables; they display an overall structure similar to Unicode encoding of emoji. Finally, more coded variables are set to account for broader compositions, since coding systems available so far are not flexible enough to accommodate the encoding of Aztec units.